The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1176/appi.ajp.2011.11030347
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Mortality Among Individual Antipsychotics in Patients With Dementia

Abstract: Objective The use of antipsychotics to treat the behavioral symptoms of dementia is associated with increased mortality. However, there remains limited information regarding individual agents’ risks. Method This was a retrospective cohort study using national data from the US Department of Veterans Affairs (fiscal years 1999–2008) for patients ≥65 years old with dementia, beginning outpatient treatment with an antipsychotic (risperidone, olanzapine, quetiapine, and haloperidol) or valproic acid and its deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
222
2
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 328 publications
(247 citation statements)
references
References 31 publications
11
222
2
6
Order By: Relevance
“…Kales et al [46] in an outpatient study comparing the mortality risk of different psychotropics suggested that haloperidol had the highest risk in the first 30 d and quetiapine the lowest. Additionally, the highest mortality risk for risperidone, olanzapine, quetiapine, and valproate is in the first 120 d of use.…”
Section: Discussionmentioning
confidence: 99%
“…Kales et al [46] in an outpatient study comparing the mortality risk of different psychotropics suggested that haloperidol had the highest risk in the first 30 d and quetiapine the lowest. Additionally, the highest mortality risk for risperidone, olanzapine, quetiapine, and valproate is in the first 120 d of use.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Medications often result in adverse effects such as increased risk of mortality, excessive sedation, increased risk of falls, lethargy, and disorientation. [18][19][20][21][22] 1.3 Rationale for non-pharmacological approaches The use of psychotropic medications to reduce aggression overlooks the possibility that aggression may be related to environmental factors and may serve a communicative function for the PWD. For example, aggressive behaviors occur most frequently during ADLs such as bathing, dressing, and toileting, which naturally involve physical touch from a caregiver.…”
Section: Prevalence Of Aggression In Pwdsmentioning
confidence: 99%
“…Длительное наблюдение пациентов, страдающих БА и принимающих антипсихотические средства, показывает, что они умирают быстрее, чем остальные пациенты [19,20]. Назначение нейролептиков наиболее опасно пациентам с БА, страдающим сердечно-сосудистыми и легочными заболеваниями.…”
Section: лечение психотических расстройств и депрессииunclassified